Diagnostic Validity of Trans-Abdominal Ultrasound for Splenic Injuries in Trauma Patients Taking CT Scan Findings as Gold Standard - Mehak; Ali, Azmat (Indus Journal of Bioscience Research, 2025)
Background: Splenic injuries commonly occur in patients with blunt abdominal trauma, especially in those involved in motor vehicle accidents and fall injuries. It is important to make an early diagnosis because any delay may lead to considerable blood loss, which may compromise the outcome in the patients. Though it has been widely accepted that the gold-standard technique in the diagnosis of splenic injuries is the application of computed tomography, access to this facility may be limited in many emergency departments. Trans-abdominal ultrasonography is frequently used as the first technique to evaluate the patients. Objective: To assess the diagnostic accuracy of ultrasound for detecting splenic injuries in trauma patients, using CT scan findings as the gold standard. Study Design and Setting: This was a cross-sectional validation study conducted from January 2025 to May 2025 in the Department of Radiology at Ayub Teaching Hospital Abbottabad. Methodology: A total of 104 trauma patients aged 18 to 60 years with blunt abdominal injury were included. Ultrasound findings were compared with computed tomography scan results. Data were analyzed using chi-square test and two by two contingency table to calculate sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy. Results: The mean age of patients was 36.02 ± 9.90 years. Trans-abdominal ultrasound showed sensitivity of 85.71%, specificity of 95.18%, positive predictive value of 81.82%, negative predictive value of 96.34% and overall diagnostic accuracy of 93.27%. Conclusion: Trans-abdominal ultrasound is a reliable and accurate tool for initial evaluation of splenic injuries in trauma patients.